(untitled) (Educational Dimension, 2022)
The relevance of the chosen research topic stems from its development outcomes, which aim to resolve contradictions between society’s needs for personality-oriented training in Physics and Mathematics basics at comprehensive secondary school and the insufficient basic (necessary and sufficient) conditions to provide this in primary grades. Teachers also lack a structured and academically supported method of immersing pupils in a didactic fairy tale atmosphere. The primary goal of the study is to present the author’s conceptual vision of the essence and principles of didactic fairy tale creation in order to transform it into a basic instrument for teaching Physics and Mathematics to 1st–4th-grade students.